Glycoprotein Synthesis and Secretion by Mucosal Biopsies of Rabbit Colon and Human Rectum - Richard P. MacDermott; Robert M. Donaldson Jr.; Jerry S. Trier (The Journal of Clinical Investigation, 1974)
Elucidation of mechanisms involved in the control of colonic production of mucus requires direct examination of glycoprotein synthesis and secretion by colonic mucosa. In the past, the limited viability of intestinal mucosa in vitro has hampered such investigations. When maintained in an organ culture system, mucosal biopsies of rabbit colon and human rectum remained viable for 24 h as documented by morphologic appearance and a steady rate of protein synthesis and secretion. These biopsies also incorporated 14C-labeled glucosamine into tissue glycoproteins and secreted labeled glycoproteins at a steady rate for 24 h. Glucosamine was predominantly incorporated into macromolecules that were ultimately secreted, in contrast to leucine, which was predominantly incorporated into tissue macromolecules. When studied by autoradiography, cultured rabbit colonic biopsies synthesized and secreted glycoproteins in vitro at cellular sites and over a time-course similar to those previously described for the intestine of intact animals. Acetylcholine consistently stimulated secretion of labeled glycoproteins but did not alter glycoprotein synthesis. In contrast, cycloheximide inhibited glycoprotein synthesis but had no effect on the secretion of newly synthesized glycoproteins. Rectal biopsies from patients with active ulcerative colitis incorporated increased amounts of [14C]glucosamine into glycoproteins during organ culture and secreted labeled glycoproteins more rapidly into the incubation medium when compared to biopsies obtained from healthy volunteers These findings indicate that organ culture provides a useful means of directly examining the synthesis and secretion of glycoproteins by healthy and diseased colonic mucosa. Images